1974
DOI: 10.1002/pssb.2220640106
|View full text |Cite
|
Sign up to set email alerts
|

Exciton and Low‐Energy Interband Structures in SrO and BaO

Abstract: Optical reflectivity data are given in the energy region 3.5 to 10 eV on freshly cleaved single crystals of SrO and BaO. The main exciton structures are interpreted in terms of two different k-space excitations one a t the zone center, the other at the edge X. Also fine structure near the SrO exciton doublet is observed.On a mesir8 la reflexion optique dans I'intervaIIe spectra1 3,5 A 10 eV de SrO et BaO monocristallins. Les cristaux ont Btb clives en vide. Le principales structures excitoniques ont Bttt inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…Also the dielectric functions of TiO 2 and SrO films are given. The optical band gaps of the two binary oxides, ~3.3 eV for TiO 2 and >5 eV for SrO, were in good agreement with the values reported in the literature (20) (21). The dielectric functions of as-deposited STO films were homogeneously distributed between the dielectric functions of TiO 2 and SrO indicating that mixtures of the two binary oxides were deposited in the amorphous phase.…”
Section: Resultssupporting
confidence: 80%
“…Also the dielectric functions of TiO 2 and SrO films are given. The optical band gaps of the two binary oxides, ~3.3 eV for TiO 2 and >5 eV for SrO, were in good agreement with the values reported in the literature (20) (21). The dielectric functions of as-deposited STO films were homogeneously distributed between the dielectric functions of TiO 2 and SrO indicating that mixtures of the two binary oxides were deposited in the amorphous phase.…”
Section: Resultssupporting
confidence: 80%
“…Indeed, Fano [12] has also shown that the antiresonance is smoothed out in the presence of two or more continua. The observed reflectance spectrum of BaO just below 2800 A [5] is characteristic of Mn interband transitions, and we assign the r,-X$ interband edge a t 4.28 eV (2800 A) and obtain x 252 meV for the binding energy of the r-excitons. We have found no reasonable basis to assign the small structures observed a t 3.862 eV (IT) and 3.85 eV (IV).…”
Section: High-energy Componentmentioning
confidence: 89%
“…The initial interpretation by Whited and Walker [3] of the low-energy set of reflectivity doublets in both MgO and CaO, was in terms of the exciton-phonon complex (EPC) initially introduced by Liang and Yoffe [6] in the interpretation of ZnO spectra. Later work by Kearney et al [5] pointed out that an EPC could not account for the similar low-energy doublet observed in their work on SrO. Their main SrO exciton structure was interpreted in terms of two different transitions (one a t I' and the other a t X ) ; it was suggested that these transitions could also account for the observed CaO and MgO structures.…”
Section: Introductionmentioning
confidence: 87%
“…The optical band gaps of the two binary oxides, ∼3.3 eV for TiO 2 and >5 eV for SrO, were in good agreement with the values reported in the literature. 34,35 Figure 4 shows that the dielectric functions of the as-deposited STO films are all distributed in a logical compositional order, and lie between the dielectric functions of TiO 2 and SrO indicating that mixtures of the two binary oxides were deposited in the amorphous phase. The values for the refractive index n (at 1.96 eV) of all STO films deposited in the FlexAL-A reactor with different [SrO]/[TiO 2 ] cycle ratios are shown in Figure 5a and were obtained from the dielectric function values through the relations:…”
Section: Plasmamentioning
confidence: 99%